A COMPREHENSIVE APPROACH TO ANALYZING WORK MOTIVATION TO IMPROVE EMPLOYEE PRODUCTIVITY AT PT BANK DKI JAKARTA - Esti Suntari; Haryantini Haryantini; Styo Budi Utomo (International Journal Multidisciplinary Science, 2025)
This study examines the impact of work motivation on employee productivity at PT Bank DKI Jakarta. In today's competitive business environment, motivation plays a crucial role in determining employee performance, engagement, and satisfaction. The research identifies key internal factors influencing motivation, including salary, interpersonal relationships, career development opportunities, work environment, and work-life balance. A preliminary survey conducted among 21 employees revealed that salary and interpersonal relationships are the primary motivational factors. Employees face challenges in career advancement and recognition, which affect their overall productivity and job satisfaction. Using a qualitative descriptive approach, this study explores how these factors shape motivation and influence performance outcomes. Findings indicate that employees who receive adequate compensation, career growth opportunities, and a positive work environment exhibit higher commitment and productivity. The study suggests that PT Bank DKI Jakarta should adopt a holistic strategy to enhance employee motivation, incorporating competitive salaries, structured career development programs, recognition initiatives, and work-life balance policies. By addressing these factors, the bank can improve workforce engagement, reduce turnover rates, and boost overall productivity. This research provides insights for organizations aiming to optimize human resource management and sustain long-term business growth.